Moderation effect of age on behaviour intention to adopt climate change information among smallholder farmers in the northern region of Ghana - Alidu, Abdul-Fatahi (2022)
Agriculture is the primary livelihood source for over 1.3 billion rural smallholder farmers’ worldwide. These smallholder farmers are vulnerable globally to the climate change because of variations in temperature and precipitation and also frequency and extremely intense events of the weather affect their income, food security well as their well-being. Some institutions and companies have started disseminating climate information to farmers to enable them effectively and successfully mitigate and adapt to the dangers of climate change. This study mainly aims at determining how climate information access influence rural smallholder farmers’ decision to adopt climate smart adaptation activities and investigating behaviour intention to adopt climate information using the UTAUT model with the moderation effect of age. Exactly 475 respondents were interviewed with structured questionnaire using multistage proportionate sampling technique. Descriptive statistics, bivariate probit, correlation analysis, multiple linear regression, and structural equation model were applied. It is revealed that most of the farmers are illiterate and married. Age, income, extension services accessibility, and assets were positively and significantly associated with smallholder farmers’ joint decision to access climate information and as well espouse climate smart adaptation strategies. The size of household was negatively and significantly related to the decision of smallholder farmers to jointly access information about climate change and to adopt climate-smart adaptation strategies. Performance and effort expectancies, as well as facilitating conditions and social influence, have a positive and moderate relationship with intended behaviour to adopt climate information while affordability had a negative and moderate relationship with intended behavior to espouse climate information. The structural equation model results indicate that performance and effort expectancies, as well as social influence, are positively and significantly related to behaviour intention to adopt climate information while affordability is significant and negatively affects behaviour intention. The effect of performance expectancy, facilitating conditions, social influence and affordability on behaviour intention to adopt climate information are moderated by age. Climate information should be made very simple and packaged in the smallholder farmers’ local languages since the majority of them are without formal education. Those providing climate information services should make it less costly since smallholder farmers are mostly poor people with less income. Extension agents should also do more in educating smallholder farmers about issues of climate change and how to get over its challenges in order to improve their livelihoods.